SISTEM INFORMASI LAYANAN ADMINISTRASI DESA KOTO TENGAH SEMERAP BERBASIS WEB - Nurjani, Yeni; Inda Aditya, Meydi (FORTECH (Journal of Information Technology), 2023)
The Koto Tengah Semerap Village Office is a government agency at sub-district level, until now it still has several problems in data management, one of which is that the process of submitting correspondence for the benefit of residents is still manual and has the effect of requiring a long processing time until the letter is completed, because residents have to come to at the village office repeatedly, namely at the time of delivery and at the time of collecting the letter. Another problem is that when storing citizen data, it is still manual and can result in documents being damaged, lost and the risk of data not being updated. For this reason, it is necessary to have an information system that can be accessed by interested parties, both within the village and outside the village environment. The design of this system aims to implement and develop an information technology system as a platform for digitizing document submission in Koto Tengah Semerap Village, in order to overcome or minimize errors in the document recording process for local communities and shorten the time associated with administrative services to make it easier, faster and more efficient. In designing this website-based document management information system, the system development method used is Rapid Application Development and the PHP programming language.